The Difference in Protein and Zinc Intake in Stunted and Non-Stunted Toddlers in Dawarblandong District, Mojokerto - Rizqy Abidah Ramdlaniyah; Choirul Anna Nur Afifah (Jurnal EduHealth, 2023)
Stunting is a health problem caused by several factors, one of which is a lack of nutrition in the long term. The nutrients that have been linked to influencing the incidence of stunting are protein and zinc. Protein is a macronutrient containing essential amino acids that are useful for growth, cell turnover, and maintenance of the body. Zinc is also useful for growth because zinc plays a role in the metabolism of Growth Hormone (GH). This study aims to determine differences in protein and zinc intake in stunted and non-stunted toddlers in Dawarblandong District, Mojokerto Regency. The type of research used is quantitative with an observational method and a case-control research design. The total sample was 54 toddlers consisting of 27 stunted toddlers and 27 non-stunted toddlers who were selected using a purposive sampling technique. Protein and zinc intake of toddlers were taken through 24-hour food recall interviews for three days and then the data were analyzed using the Wilcoxon Rank Sum Test. The results showed that there was a significant difference in protein intake (p value 0.014) and zinc intake (p value 0.020) between stunted and non-stunted toddlers. This difference in intake is thought to be influenced by differences in toddler eating patterns. Stunted toddlers consume more plant-sourced foodstuffs than animal-based ones, while non-stunted toddlers consume a combination of foods from plant and animal sources in a day's meal so that the nutrients they get are better. This difference in eating patterns is associated with differences in the parenting style of each toddler where mothers of non-stunted toddlers understand more about intakes that are rich in nutrients that are useful for children's bodies and are more patient in controlling children's eating patterns. Meanwhile, the parenting style of stunted toddler mothers frees the child to choose whatever food the child likes even though the food has less nutritional value.